Measurement of the top quark-pair production cross section with ATLAS in pp collisions at √ s = 7 TeV - Anduaga, Xabier Sebastián (2011)
A measurement of the production cross-section for top quark pairs (t¯t) in pp collisions at √ s =7 TeV is presented using data recorded with the ATLAS detector at the Large Hadron Collider. Events are selected in two different topologies: single lepton (electron e or muon μ) with large missing transverse energy and at least four jets, and dilepton (ee, μμ or eμ) with large missing transverse energy and at least two jets. In a data sample of 2.9 pb−1, 37 candidate events are observed in the single-lepton topology and 9 events in the dilepton topology. The corresponding expected backgrounds from non-t¯t Standard Model processes are estimated using data-driven methods and determined to be 12.2 ± 3.9 events and 2.5 ± 0.6 events, respectively. The kinematic properties of the selected events are consistent with SM t¯t production. The inclusive top quark pair production cross-section is measured to be σt¯t = 145±31(stat.) +42 −27(syst.) pb. The measurement agrees with perturbative QCD calculations.